(untitled) (Eurasian Journal of Ecology, 2023)
The manuscript presents the results of monitoring during the introduction near the capital of Kazakhstan of trees plants imported from China and planted in the nursery of the Akkol State Forestry Enterprise in the northern part of the Akmola region. Fraxinus Bungeana, Fraxinus Americana, Populus Euphratica were used as the object of study in the experiment. The adaptive characteristics of the selected plants were compared according to various bioecological indicators. Taxation and biometric indicators of these trees amounted to 60.1; 47.7; 22.3 percent. In samples of tree leaves of different sizes, the level of photosynthetic activity was determined. This indicator among the studied species was the lowest in Populus Euphratica (0.63 µg/g), average in Fraxinus Americana (0.76±0.01) and high in Fraxinus Bungeana (0.80 µg/g). The resistance of trees plants to the new environment was assessed by the amount of accumulation of heavy metals in their leaf blades. An increased concentration of copper and iron accumulated American ash, Bunge ash. The content of cadmium, lead, zinc did not exceed the MPC. In general, the monitoring showed that different types of trees introduced in the vicinity of the city of Nur-Sultan in the north of the Akmola region show different adaptive responses. It is shown that heavy metals accumulate more intensively in ash leaves. Populus Euphratica turned out to be the most resistant to this ecological environmental factor, and Fraxinus Bungeana is the most sensitive among ash representatives. In general, the adaptation of trees introduced from abroad in the region of northern Kazakhstan, near the city of Nur-Sultan, is carried out in accordance with their biological characteristics. It has been observed that Populus Euphratica is more resistant and Fraxinus Bungeana is the most sensitive species when introduced. In general, based on our research, an algorithm for short-term monitoring of introduced trees has been developed to preserve the biodiversity of ornamental plants. Key words: China, tree plants, nurseries, Northern Kazakhstan, introduction, photosynthesis, heavy metals crops